Discursos sobre el hacinamiento: una oportunidad para reflexionar sobre el conflicto - García García, Sergio (Cuadernos de Trabajo Social, 2006)
The following article seeks to contribute to the supply of knowledge about social context required by the categories that social intervention professionals use. Delving into the intellectual production related to the phenomena of social exclusion in contemporary societies offers us the opportunity to go more deeply into the relationship between residential exclusion and immigration. Since housing is one of the most highly valued material objects in our society (increasing value in proportion to the restriction placed by the mechanisms of the market on access to housing) and immigrants comprise the group that historically has found greatest difficulty in the use of housing, an analysis of overcrowding as a manifestation of the precarious state of housing provides us the opportunity to reflect on the perception of the public and private space that inhabitants of cities have and on the intercultural relationships that different social groups establish between themselves, as well as the community of social intervention professionals and the foreign population.